Simultaneously Passivating Cation and Anion Defects in Metal Halide Perovskite Solar Cells Using a Zwitterionic Amino Acid Additive. Issue 3 (23rd December 2020) - Kim, Ju‐Hyeon; Kim, Yong Ryun; Park, Byoungwook; Hong, Soonil; Hwang, In‐Wook; Kim, Jehan; Kwon, Sooncheol; Kim, Geunjin; Kim, Heejoo; Lee, Kwanghee
Abstract: Ionic defects (e.g., organic cations and halide anions), preferably residing along grain boundaries (GBs) and on perovskite film surfaces, are known to be a major source of the notorious environmental instability of perovskite solar cells (PeSCs). Although passivating ionic defects is desirable, previous approaches using Lewis base or acid molecules as additives suppress only the negatively or positively charged defects, thus leaving oppositely charged defects. In this work, both the cationic and anionic defects inside methyl ammonium lead tri‐iodide (MAPbI3 ) are simultaneously passivated by introducing a zwitterionic form of the amino acid, L‐alanine, into the precursor solution as an additive. L‐alanine has both positive (NH3 + ) and negative (COO − ) functional groups at a specific solvent pH, thereby passivating both the cation and anion defects in MAPbI3 . The addition of L‐alanine increases the grain size of the perovskite crystals and lengthens the charge carrier lifetime (τ > 1 µs), leading to improved power conversion efficiencies (PCEs) of 20.3% (from 18.3% without an additive) for small‐area (4.64 mm 2 ) devices and 15.6% (from 13.5%) for large‐area submodules (9.06 cm 2 ). More importantly, the authors' approach also significantly enhances the shelf storage and photoirradiation stabilities of PeSCs. Abstract : A novel strategy to neutralize charged point defects in organic‐inorganic hybrid perovskite materials is proposed for highly efficient and stable perovskite solar cells by using a zwitterionic L‐alanine additive, which can be passivated simultaneously with both positively and negatively charged defects because it contains both anion and cation functional groups in one molecule.